Temps : The Many Faces of the Changing Workplace - Krasas, Jackie, 1965- (Book collections on Project MUSE., 2000)
Now firmly established as fixtures of the American workplace, temporary employees constitute a much-discussed but still poorly understood segment of the labor force. In this consciousness-raising book, Jackie Krasas Rogers explores the realities of temporary work from the points of view of workers, agencies, and clients, focusing especially on issues of race, gender, power, and identity. Rogers investigates the situations of two very different kinds of temporary worker-lawyers and those in clerical settings-and finds contrasts and similarities between the two groups' reasons for seeking temporary work, the type of tasks performed, and the value attached to that labor. The goals of temporary workers can be at odds with the interests of the agency and the client, the other players in the power triad of "temping." Where clerical workers often see temporary employment as a stepping stone to a permanent job, many find upward mobility more illusory than real. Because temporary workers can be called in and let go at will or whim, and they have no established social relations in the workplace, they often work harder than permanent workers. Rogers, one of the authoritative scholars of temporary work in the United States, uses extensive archival and field data-including notes from her own work as an office temporary-to put a face on America's temporary workforce